A guide to vertebrates of bajo de la Alumbrera, Catamarca, Argentina - Autino, Analia Gladys (2014)
Books are a celebration. A book on biodiversity is twice a celebration. This guide on Bajo de la Alumbrera native vertebrates is a major literary work in terms of scope and presentation of the information. The topic is well known to the authors as they have previously written a very useful university manual on biodiversity. The purpose of this guide was presented in the introduction. This book is generally structured as a detailed list of the species that may be found in the area, including a brief description of the target area. Out of the total species listed, ranging from fish to mammals, some have been selected for individual discussion. Like the wildlife encyclopaedias that led my vocation, this guide is composed of depictions, including world-class information and pictures. It describes the main clusters of vertebrates that may be found at Bajo de la Alumbrera among other areas since, as shown in provincial and Argentine maps, some species are also found in other locations. At the top of each depiction are the common and scientific names of the species and its biological classification. The size of typical specimens as well as their conservation status, food habits and pattern of rest and activity are specified using a practical set of symbols. In some special cases, more than one species is included in each depiction, for instance several species are named as snake or lizard. A detailed map shows the geographic distribution of each species. This costly book presents valuable information on the major 93 species under a simple classification: from the most to the least abundant/observed. Each depiction includes a brief description, distribution (including the habitat or preferred location), biological features and conservation status as well as first-rate pictures and outstanding illustrations. Naturalists have always used arts as a communication tool reflecting typical archetypes which, as Jorge Luis Borges put it, are ?detached and derisive?. Thus, this Guide on Bajo de la Alumbrera Vertebrates supports artistic talent as a key to intellectual capitalism, which in the opinion of scientific futurists such as Michio Kaku, will be a major challenge for nations and individuals during the XXI century.